Asymmetric Exchange Rate Pass-Through to Domestic Price Indexes with the Approach of SVAR - Javid Bahrami; Teimour Mohammadi; Shadi Bozorg (فصلنامه پژوهش‌های اقتصادی ایران, 2014)
Tracing the impact of exchange rate movements on prices is one the most important issues in monetary policy making. In this paper by applying a SVAR model to a quarterly data set spanning from 1990q1 to 2013q4, we assess the effect of exchange rate variations on domestic prices in Iran. In addition to exchange rate growth and output gap, the growth of liquidity, consumer, producer, and import prices are also included in the model. Our findings suggest that: i) There is an asymmetry in exchange rate pass-through in Iran. ii) Although small appreciations have no effect on prices, depreciations, especially large ones, are significantly effective. iii) The effect of exchange rate on consumer price growth, lasts for relatively longer periods of time.